A Modified Endoscopic Transforaminal Lumbar Interbody Fusion Technique: Preliminary Clinical Results of 96 Cases - Gong, Junfeng; Huang, Zheng; Liu, Huan; Zhang, Chao; Zheng, Wenjie; Li, Changqing; Tang, Yu; Zhou, Yue (Frontiers in Surgery, 2021)
Background As a newly emerging technique, percutaneous endoscopic lumbar interbody fusion (PELIF) has become an increasingly popular procedure of interest. The purpose of this study was to introduce a novel PELIF system and share our preliminary clinical experiences and outcomes in treating lumbar degenerative disease with this procedure. Methods Ninety-six patients (thirty-seven men and fifty-nine women; mean age 55.85±11.03 years) with lumbar degenerative diseases who underwent PELIF in our hospital were enrolled. The surgical time, volume of intraoperative blood loss, postoperative hospitalization time and postoperative drainage were documented. Clinical outcomes were evaluated by visual analog scale (VAS) scores, Oswestry Disability Index (ODI) scores, and modified MacNab criteria. Bone fusion was identified through computerized tomography (CT) scans or X-ray during the follow-up period. Results All patients were followed up for at least 12 months, and the average follow-up time was 17.03 ± 3.27 months. The mean operative time was 136.79±30.14 minutes, and the mean intraoperative blood loss was 53.06±28.89 ml. The mean VAS scores of low back pain and leg pain were 5.05±1.37 and 6.25±1.03, respectively, before surgery, which improved to 2.27±0.66 and 2.22±0.55, respectively, after the operation (P<0.05). The final VAS scores of low back pain and leg pain were 0.66±0.60 and 0.73±0.66, respectively (P<0.05). The preoperative ODI score (49.06±6.66) also improved significantly at the 3-month follow-up (13.00±7.37; P<0.05). The final ODI score was 8.03±6.13 (P<0.05). No cases of nonunion were identified by imaging at the follow-up. Conclusions The present study demonstrated satisfactory clinical and radiologic results among patients who received PELIF treatment from our institution. This indicates that PELIF is efficient and safe for select patients.